A systemic functional analysis of two multimodal covers - Martínez Lirola, María (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2006)
Our society is influenced by new texts, which are clearly characterised by the increasing dominance of the visual mode; this implies that new literacies need to be developed as a way of enabling the readers to question the texts they are exposed to. We argue for a multimodal and situated approach for understanding and interpreting writing on magazine covers because they are examples of an increased emphasis on modes of representation other than the written, especially an increased dominance of the visual mode. This is the reason why we are going to analyse two covers of free British magazines (published in London on July 14, 2003) to see the different resources they use to attract people's attention and to encourage readership, particularly because they were delivered at the exit of underground stations. Systemic Functional Linguistics will be our theoretical framework in this article because for this linguistic school the text is the basic unit of analysis and it studies language in relation to society. SFL will help us to understand why a text is written as it is by paying attention to its context and textual organisation.